Maintaining Equitable and Inclusive Classroom Communities Online During the COVID-19 Pandemic - Sarah Elizabeth Barrett (University of Windsor, 2021)
This paper explores the ways in which face-to-face classroom communities were disrupted and/or transformed by the move to online platforms and the effect of this disruption on equitable access to a quality education. Quality education is defined as engaged pedagogy, where students learn to interact with other students and engage with ideas in a way that promotes their ability to be part of a community while still feeling free to disagree with, critique, and take care of each other. To examine the extent to which such communities were created when schooling migrated online during the pandemic, this paper examines online schooling communities in terms of sense of belonging, trust, shared purpose, and quality of interactions. The analysis of the experiences of 11 teachers in Ontario, Canada, whose face-to-face classes were moved to online formats, establishes that equity was one of the first casualties of the change, with the most vulnerable students facing disproportionate academic, psychological, and social consequences.